Economic policy uncertainty and cross-border mergers and acquisitions - Paudyal, Krishna; Thapa, Chandra; Koirala, Santosh; Aldhawyan, Sulaiman (Journal of Financial Stability, 2021)
We examine the effects of economic policy uncertainty (EPU) on cross-border mergers and acquisitions (CBAs). The results show that a higher degree of EPU at home retards the number and volume of inbound CBA deals. However, this effect is positively moderated by the host country’s better quality of institution, business environment and political risk. The bilateral acquirer-target country-pair investigation reveals that while higher EPU in the target’s domicile deters inbound CBAs, higher EPU in the acquirer’s nation is positively associated with a higher number and volume of outbound CBA deals. Finally, on the announcement of the deals, targets (acquirers) based in countries with a larger increase in EPU are associated with lower (more) stock returns than the targets (acquirers) based in countries with a smaller increase in EPU. These findings imply that countries aiming to attract cross-border investments should strive to mitigate economic policy-related uncertainties.